Краткий экскурс в раннюю историю изучения паремии как объекта этнолингвистики - Штейнгольд, Анжелика (Slavistica Vilnensis, 2012)
Как хорошо известно, пословицы и поговорки (в более общем смысле т. наз. паремии) являются не только художественными миниатюрами — анонимными произведениями устного народного творчества, употребление которых в речи диктуется потребностью в точности и выразительности, но также неписаным сводом этических норм и правил. Их назидательность и дидактичность во многом предопределяет существование особой “паремической” логики, на языковом уровне выражающейся в присущей пословицам и поговоркам специфической синтаксической оформленности. На поверхности лежит их семантическая многлоплановость, о чем в свое время писали А. Дандис [1978], А. Крикманн [1978; 1984], Ю.И. Левин [1984], Г.Л. Пермяков [1988] и др. ... Anzhelika Shteingold On the Early History of Proverb Studies (Proverb as an Object of Ethnolinguistics) It is often not clear what exactly is meant by certain words and constructions in a proverb, even though its actual (metaphorical) sense is understood. The origins of some historical proverbs might be grasped only by employing the data of cultural anthropology. In the present article a short overview of early proverb studies in Russia is given. In the nineteenth century and in the early part of the twentieth century there were many scholars in Russia who dealt with proverbs. For instance, I. Snegiryov, V. Dahl, F. Buslaev, A. Afanasyev, A. Potebnya, S. Maksimov. During the 1930’s this tradition was continued in the scientific papers of the academician J. Sokolov. Despite their methods of proverb studies not being contemporary, these researchers gave examples of etymology that would later receive support and approval from the scholars of our time. Keywords: Russian proverbs, ethnolinguistics, etymology, history of proverb studies.